Exploring Generation Z Consumers’ Manners on Green Purchase Behavior Regarding Reusable Product - Oprilyani, Adhinda Dwi; Malini, Helma; Barkah; Listiana, Erna; Setiawan, Harry (Yayasan Sinergi Kawula Muda, 2025)
This research examines Generation Z's attitudes towards green purchasing behavior, with particular attention to the use of reusable products, amidst the growing issue of plastic waste in Indonesia. Generation Z's particular drive to choose sustainable purchasing provides an in-depth look at green consumption patterns. In the face of major challenges from single-use plastics, this study analyzes the influence of environmental concern and green brand knowledge on Generation Z's intention and action to purchase reusable products. Unlike previous research, this study pays special attention to generation Z, a group that has rarely been the focus in discussing the influence of these factors. A total of 264 generation Z respondents in Pontianak were surveyed in this study, which was analyzed through a quantitative approach using SEM with the help of SmartPLS 3 software. This study found that environmental concern and green brand knowledge significantly influence green purchase intention, which in turn positively influences green purchase behavior, with green purchase intention as a key mediator. The results indicate that a strategic approach that promotes environmental concern and green brand knowledge has the potential to encourage green consumption behavior and support sustainable practices.